Estudo comparativo entre modelagem bidimensional e tridimensional utilizando métodos construtivos para vestuários femininos - Machado, Dyane keyla (2022)
Modeling is a fundamental technique to guarantee the clothing development process. In industry, there are basically two geometric methods of modeling articles, the flat pattern and draping techniques, which can be developed manually or through a digital computer aided design system, in addition to constructive methods to create volume and shape in garments. This work aimed to compare the 2D and 3D modeling methods using constructive methods applied to the development of women's clothing with different textile materials, analyzing the variables – execution time, methodology, aesthetic result and prototype wearability; involved in the mold construction process.The methodology was carried out through the development of prototypes using 2D and 3D modeling techniques and constructive methods; data collection will be done during the stages and after the prototypes are completed, using a timer and application of tools: questionnaire and checklist. Despite, it was found that the applied modeling methodology is able to influence the fit of the model in the prototype, as well as the textile material used. The execution time of the methodologies varied between 5.5 and 10 hours for the 2D and 3D models, respectively; however, it was noted that the aesthetic and wearability characteristics of the samples made in the draping were superior to the flat pattern. It is concluded that the flat pattern has a limitation of models, however, shorter execution time, allowing profit in large scales and; the draping reveals exceptional fit and allows personalized creations, meantime, it takes time, nevertheless, as it adds value.